2011
DOI: 10.1242/jeb.044487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grade and mass distribution on the mechanics of trotting in dogs

Abstract: SUMMARYQuadrupedal running on grades requires balancing of pitch moments about the center of mass (COM) while supplying sufficient impulse to maintain a steady uphill or downhill velocity. Here, trotting mechanics on a 15deg grade were characterized by the distribution of impulse between the limbs and the angle of resultant impulse at each limb. Anterior-posterior manipulation of COM position has previously been shown to influence limb mechanics during level trotting of dogs; hence, the combined effects of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 43 publications
(62 reference statements)
5
40
1
Order By: Relevance
“…This result is consistent with the heightened role of the hindlimbs in providing support and propulsion on inclined terrain (e.g. Lee, 2011).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This result is consistent with the heightened role of the hindlimbs in providing support and propulsion on inclined terrain (e.g. Lee, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…These studies have confirmed, for example, that ground reaction forces (GRFs) are re-distributed between the forelimbs and hindlimbs with changes in surface grade; the forelimbs typically provide increased support and braking on a downslope, while the hindlimbs provide increased support and propulsion on an upslope (e.g. Dutto et al, 2004;Gregor et al, 2006;Lammers et al, 2006;Lee, 2011). Cats have been shown to generate increased extension moments at the hip, knee and ankle when walking on an upslope and decreased moments at the hip and ankle when walking on a downslope (Gregor et al, 2006), which is consistent with re-distribution of the GRFs and reorientation of the resultant force vectors.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition to the elevated incline cost imposed by changes in muscle contractile behaviour, there may be a reduction in the force-generating capacity of the locomotor muscles as a result of altered limb posture (Higham and Biewener, 2008). Such changes have been observed in a number of quadrupedal species (Carlson-Kuhta et al, 1998;Lammers et al, 2006;Lee, 2011;Vilensky et al, 1994). Although posture was not quantified in the present study, the intercepts of the lines relating P met to U have been postulated to represent a 'postural cost' separate from the cost of moving and that of resting metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Although the hindlimbs are the key propulsors in terrestrial vertebrates, with the forelimbs absorbing collisional energy and acting primarily as brakes (Lammers and Biknevicius, 2004;Autumn et al, 2006;Lee, 2010;Deban et al, 2012), the coordinated function of the forelimbs and the hindlimbs is poorly understood in arboreal vertebrates. Structural differences between the forelimbs and the hindlimbs have been well documented among vertebrates; the pectoral girdle is generally more mobile than the pelvic girdle and structural differences between the glenoid cavity and the acetabulum lead to the potential for a greater range of motion in the forelimb than in the hindlimb (Haines, 1952;Snyder, 1954;Peterson, 1971;Peterson, 1973;Peterson, 1974;Jenkins and Goslow, 1983;Peterson, 1984;Reynolds, 1985;Schmitt, 1994;Larson et al, 2001;Lammers, 2007;Zihlman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%